Analysis of Plastic Surgery Consultations in a High-Volume Paediatric Emergency Department: A Quality Improvement Initiative. Issue 4 (November 2021) - Neuhaus, Kathrin; Ho, Emily S.; Low, Nelson; Forrest, Christopher R.
Introduction: Consult services influence emergency department (ED) workflow. Prolonged ED length of stay (LOS) correlates with ED overcrowding and as a consequence decreased quality of care and satisfaction of health team professionals. To improve management of paediatric ED patients requiring plastic and reconstructive surgery (PRS) expertise, current processes were analyzed. Methods: Patient characteristics and metrics of PRS consultations in our paediatric ED were collected over a 3-month period. Data analysis was followed by feedback education intervention to ED and PRS staff. Data collection was then resumed and results were compared to the pre-intervention period. Results: One hundred ninety-eight PRS consultations were reviewed, mean patient age was 6.3 years. Most common (52%) diagnoses were burns and hand trauma; 81% of PRS referrals were deemed appropriate; 25% of PRS consults were requested after hour with no differences in patient characteristics compared to regular hours; 60% of consultations involved interventions in the ED. Time between ED registration and PRS consultation request (116.5 minutes), quality of procedural sedation (52% rated inadequate), and overall ED LOS (289.2 minutes) were identified as main areas of concern and addressed during feedback education intervention. Emergency department LOS and quality of sedation did not improve in the post-intervention period. Conclusion: The study provides detailed insights in the characteristics of PRS consultation in the paediatric ED population. Despite high referral appropriateness and education feedback intervention, significant inefficiencies were identified that call for further collaborative efforts to optimize quality of care for paediatric ED patients and improve satisfaction of involved healthcare professionals.